Agriculture 4.0: Broadening Responsible Innovation in an Era of Smart Farming - Rose, David Christian; Chilvers, Jason (Frontiers in Sustainable Food Systems, 2018)
Agriculture is undergoing a new technology revolution supported by policy-makers around the world. While smart technologies, such as Artificial Intelligence, robotics, and the Internet of Things, could play an important role in achieving enhanced productivity and greater eco-efficiency, critics have suggested that the consideration of social implications is being side-lined. Research illustrates that some agricultural practitioners are concerned about using certain smart technologies. Indeed, some studies argue that agricultural societies may be changed, or “re-scripted,” in undesirable ways, and there is precedent to suggest that wider society may be concerned about radical new agricultural technologies. We therefore encourage policy-makers, funders, technology companies, and researchers to consider the views of both farming communities and wider society. In agriculture, the concept of responsible innovation has not been widely considered, although two recent papers have made useful suggestions. We build on these interventions by arguing that key dimensions of responsible innovation—anticipation, inclusion, reflexivity, and responsiveness—should be applied to this fourth agricultural revolution. We argue, however, that ideas of responsible innovation should be further developed in order to make them relevant and robust for emergent agri-tech, and that frameworks should be tested in practice to see if they can actively shape innovation trajectories. In making suggestions on how to construct a more comprehensive framework for responsible innovation in sustainable agriculture, we call for: (i) a more systemic approach that maps and attends to the wider ecology of innovations associated with this fourth agricultural revolution; (ii) a broadening of notions of “inclusion” in responsible innovation to account better for diverse and already existing spaces of participation in agri-tech, and (iii) greater testing of frameworks in practice to see if they are capable of making innovation processes more socially responsible.